2006
DOI: 10.1007/s11745-006-5086-6
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid reduces hepatic steatosis, improves liver function, and favorably modifies lipid metabolism in obese insulin‐resistant rats

Abstract: CLA has been shown to induce or suppress excess liver lipid accumulation in various animal models. Interestingly, the state of insulin resistance may be an important modulator of this effect. The objective of the current study was to determine how feeding a dietary CLA mixture would affect liver lipid accumulation in insulin-resistant/obese and lean rats in relation to liver function, lipidemia, liver TAG and phospholipid FA composition, and expression of hepatic markers of FA transport, oxidation, and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
(52 reference statements)
5
25
1
2
Order By: Relevance
“…The adverse effects to induce fat liver and/hepatic steatosis have been also observed by other groups, and increasing studies indicate that t10, c12 isomer is the major player [9,22,97,133]. However, dietary CLA was reported to alleviate nonalcoholic fatty liver disease or hepatic steatosis in ZDF rats [134,135]. The discrepancy illustrated a relationship between the state of insulin resistance and liver-lipid metabolism, and suggested that CLA might act to favorably modify lipid metabolism in ZDF rats.…”
Section: Effects Of Pufa On the Neuroendocrine Systemmentioning
confidence: 70%
“…The adverse effects to induce fat liver and/hepatic steatosis have been also observed by other groups, and increasing studies indicate that t10, c12 isomer is the major player [9,22,97,133]. However, dietary CLA was reported to alleviate nonalcoholic fatty liver disease or hepatic steatosis in ZDF rats [134,135]. The discrepancy illustrated a relationship between the state of insulin resistance and liver-lipid metabolism, and suggested that CLA might act to favorably modify lipid metabolism in ZDF rats.…”
Section: Effects Of Pufa On the Neuroendocrine Systemmentioning
confidence: 70%
“…The protocol for the animal care procedures was approved by the University of Manitoba Protocol Management and Review Committee. Other indices for these rats related to hepatic steatosis, pancreatic function, glucose disposal, and inflammatory markers have been reported elsewhere [30,31]. The dietary formulation and the fatty acid distributions of the CLA and CTL diets have been previously reported [30].…”
Section: Animals and Dietsmentioning
confidence: 86%
“…However, rats given the t10,c12 CLA isomer had higher amounts of perirenal fat mass compared to all the other groups. We have previously observed higher relative epididymal and perirenal fat mass in younger fa/fa Zucker rats fed a CLA mixture despite no change in body weight and improvements in glycemic control, pancreatic and hepatic functions [36,66]. Greater levels of adipose mass surrounding the kidney may be related to the increased renal damage in the rats given the 10,c12 CLA diets.…”
Section: Discussionmentioning
confidence: 94%